Effects of Cellulase and Lactiplantibacillus plantarum on Chemical Composition, Fermentation Characteristics, and Bacterial Community of Pennisetum giganteum z.x.lin Silage - Zhili Wu; Xiongfei Zhang; Rongnuo Li; Jingtao Hui; Lu Deng; Inho Kim; Jie Wei; Junhu Yao; Xinjian Lei (Agriculture)
In order to explore the effects of additives on the chemical composition, fermentation characteristics, and bacterial community of Pennisetum giganteum z.x.lin silage, Pennisetum giganteum z.x.lin was ensiled with no additives (CON), cellulase (CE), Lactiplantibacillus plantarum (LP), or the combination of cellulase and Lactiplantibacillus plantarum (LPCE) at room temperature for 60 days, respectively. The results indicated that LPCE had the highest dry matter (DM) content. Compared with CON, LP exhibited higher (p < 0.05) levels of water-soluble carbohydrate (WSC), crude protein (CP), and lactic acid (LA), along with a higher (p < 0.05) ratio of LA/acetic acid (AA). Meanwhile, silage inoculated with cellulase (CE and LPCE) showed lower (p < 0.05) contents of acid detergent fiber (ADF) and neutral detergent fiber (NDF) than CON. Furthermore, additive treatments improved the bacterial community composition of silage, and Lactobacillus was abundant in LPCE (LDA score > 4.0). Compared with CE and LP, LPCE more effectively promoted the transformation of microbial functions, resulting in an upregulated (p < 0.05) carbohydrate metabolism and a downregulated (p < 0.05) membrane transport. In conclusion, cellulase or Lactiplantibacillus plantarum improved the silage quality of Pennisetum giganteum z.x.lin by reducing the fiber content or enhancing LA fermentation, and their combination exhibited a powerful ability to establish a bacterial community dominated by Lactobacillus, which facilitated the production of high-quality silage.